Synthesis of polycyclic spiroindolines by highly diastereoselective interrupted Ugi cascade reactions of 3-(2-isocyanoethyl)indoles. Issue 84 (3rd October 2016) - Saya, Jordy M.; Oppelaar, Barry; Cioc, Răzvan C.; van der Heijden, Gydo; Vande Velde, Christophe M. L.; Orru, Romano V. A.; Ruijter, Eelco
Abstract : We report a highly diastereoselective interrupted Ugi reaction to construct a broad range of structurally congested and stereochemically complex spiroindolines from tryptamine-derived isocyanides. Abstract : We report a highly diastereoselective interrupted Ugi reaction to construct a broad range of structurally congested and stereochemically complex spiroindolines from tryptamine-derived isocyanides. The reaction is facilitated by using fluorinated alcohols (TFE or HFIP) as solvents and tolerates a broad range of amines, aldehydes and 2-isocyanoethylindoles to give polycyclic products in moderate to excellent yields.